Effect of frequency-to-place mismatch on speech and music sound quality in acoustic cochlear implant simulation. - Villejoubert,L; Picinali,L; Faulkner,K; Vickers,D (J Acoust Soc Am, 2026)
Sound quality perception for cochlear implant (CI) users has become increasingly important. Although many CI users achieve near-normal speech recognition in quiet, they often report poor sound quality, particularly for music. One factor contributing to this degradation is frequency-to-place mismatch (FTPM), which occurs when electrode positions do not align with the cochlea's characteristic frequency map. This study aimed to better understand the impact of FTPM on sound quality in CI simulations across different signal types and configurations. Twenty-three normal-hearing participants were tested (online or onsite) using an adapted MUlti Stimulus test with Hidden Reference and Anchor (MUSHRA) paradigm. Different FTPM configurations were simulated with a noise vocoder to assess their influence on speech and music sound quality. Results showed that greater FTPM caused noticeable degradation, especially when lower frequencies were affected. Variability in FTPM across electrodes also significantly reduced perceived quality. Furthermore, the impact of FTPM depended on the type of stimulus, with speech and music showing distinct sensitivity patterns. Online assessments closely matched onsite results, confirming the reliability of remote testing. Together, these findings clarify why sound quality perception differs between CI users and contexts and highlight new opportunities to develop strategies for alleviating mismatch effects in CIs.